RIS-Aided coexistence in wireless networks using angular information - Anish Pradhan; Idban Alamzadeh; Mohammadreza F. Imani; Harpreet S. Dhillon (Scientific Reports)
Abstract Owing to the ability of reconfigurable intelligent surfaces (RISs) to control the propagation environment in their vicinity, they have emerged as an appealing solution to enhance the performance of next-generation wireless networks. While the effectiveness of RISs with complete channel state information (CSI) is well-documented, their performance with limited user information remains less explored. This is particularly pronounced when an RIS interferes with nodes in a potentially non-cooperating network, making CSI acquisition challenging. This paper focuses on such scenarios, examining the interference suppression capabilities of an RIS for coexisting secondary and primary users (SUs and PUs) using angular information, achievable even with non-cooperating PUs. We address the coexistence challenge by employing semidefinite relaxation (SDR) and inner majorization minimization (iMM) for RISs with continuous phase control, and propose an enhanced SDR tailored for discrete RISs. Numerical results reveal both SDR and iMM require at least five bits of discrete phase control for moderate interference suppression. They also indicate that interference suppression weakens if the PUs are inside certain angular regions, a limitation that varies with the algorithm but can be mitigated by increasing RIS elements. Ultimately, the coexistence performance of the RIS with a non-cooperative network is validated through full-wave simulations.